The process of government under Jefferson - Cunningham, Noble E., Jr., 1926-2007 (Princeton legacy library., 1978)
"Based on an exploration of the total mass of executive and legislative records for the years 1801-1809-something no other scholar has attempted-this thoroughly documented account describes the machinery and operation of the presidential office, the Cabinet, the departments, and other offices and commissions in the executive branch. It also explains the organization and processes of the national legislature. Cunningham has cleared away many errors and misconceptions, among them the claim that Jefferson was not interested in the normal process of day-to-day administration. In fact, Jefferson emerges as one of the most effective administrators ever to occupy the Presidency. This is an important and path-breaking study in administrative and legislative history." -Julian P. Boyd, Princeton UniversityOriginally published in 1978.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.